Impact of chronic vitamin A excess on sperm morphogenesis in mice. (29th June 2021) - Yokota, Satoshi; Sekine, Nao; Wakayama, Tomohiko; Oshio, Shigeru
Abstract: Background: The increasing availability of fortified foods and supplements has caused an overconsumption of vitamin A (VA), above the recommended level. To date, the effects of chronic VA excess (VAE) on spermatogenesis remain unclear. Objective: This study aims to investigate the long‐term excessive intake of VA effects on spermatogenesis in mice. Materials and methods: Dams were initially fed a control diet (4 IU/g) or a VAE diet (250 IU/g), 4 weeks prior to mating and during pregnancy. Dams and their male pups continued this diet regimen until the offspring reached 12 weeks of age. At 12 weeks of age, epididymis caudal spermatozoa and testes were collected. For histological analysis, sections were stained with periodic acid‐Schiff‐hematoxylin, and quantitative PCR was used to detect changes in gene expression in the testes of the VAE mice. Sperm motility and morphology were evaluated to detect the endpoint of VAE toxicity. Results: Body weights were not significantly different between the control and VAE groups. Testicular cross‐sections from the control and VAE mice contained a normal array of germ cells, and the daily sperm production was similar between the two groups. However, the percentage of seminiferous tubules in stages VII and VIII was significantly lower in the VAE mice than in the control. In addition, significant changes in the expression of genes involved in retinoid metabolism, spermatogenesis, and spermiogenesis were detected in the testes of the VAE mice. Consistently, sperm motility and head morphology were significantly impaired in the VAE mice. Discussion and Conclusion: Our findings suggest that long‐term dietary intake of VAE was able to influence both pre‐ and post‐meiotic spermatogenesis. As a result of testicular toxicity, we demonstrated, to the best of our knowledge, for the first time that long‐term VAE caused sperm‐head abnormalities.